Formulation and Evaluation of Herbal Face Scrub (International Journal of Food and Nutritional Sciences, 2022)
Herbal products or cosmeceuticals usually consist of the parts of plant which possessantimicrobial, antioxidants and anti aging properties. Natural constituents are the safest and the bestproduct to use in day to day life because they do not have any adverse effects and these cosmetics alsoinfluences the biological function of the skin. In this formulation of facial scrub sandalwood,Fuller’s earth,Neem, Turmeric , Green tea, Kalonji, Giquorice and aloe vera are used as active ingredients.